The Influence Of The Number Of Industries And Industrial Labor On Economic Growth Through Production Capacity As An Intervening Variable In Labuhan Batu Regency - Dalimunthe, Muhammad Yunus; Harahap, Isnaini; Batubara, Maryam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to analyze the influence of the number of industries and industrial labor on economic growth through production capacity as an intervening variable in Labuhan Batu Regency from 2015 to 2023. The type of research used is quantitative research. This study uses secondary data in the form of time series for the period 2015-2023 available at BPS in Labuhan Batu Regency, totaling 36 samples. Quantitative data analysis employs path analysis, processed using Eviews 10 software. Based on the t-test results, the research shows that the number of industries significantly affects production capacity, industrial labor significantly affects production capacity, production capacity significantly affects economic growth, the number of industries significantly affects economic growth, and industrial labor negatively significantly affects economic growth. Based on the Sobel test results, production capacity can mediate the number of industries on economic growth, but production capacity cannot mediate the number of industries on economic growth.